Pengaruh Iklim Mikro terhadap Respons Fisiologis Sapi Peranakan Fries Holland dan Modifikasi Lingkungan untuk Meningkatkan Produktivitasnya (ULASAN) - A Yani; B P Purwanto (Faculty of Animal Science, Bogor Agricultural University, 2006)
Most of Holstein in Indonesia were imported from European countries which have temperate climate (13-25 0C). If those Holstein were kept under high temperature and high humidity and exposed to direct solar radiation, the cattles would be experienced with heat stress, resulted in decreasing appetite, increased water intake, decreased metabolism, increased catabolism, increased heat loss through evaporation, decreased hormone concentration in blood, increased body temperature, increased respiration and heart rate and behavioral changes. To reduce the heat stress can be achieved by environment modification, such as type of animal house construction, type of roof material selected for animal house and determination of animal housing height. The improvement of environmental condition was gained for maintaining the animal heat balance in steady state, due to reducing the thermoregulatory responses (i.e heart rate, respiration rate and mean body temperature). Controlling the heat stressed animals to lower thermoregulatory activities will improve their productivity. Key words : Holstein, physiological responses, heat stress, micro-climate, environmental modification